E-scholarship system for Libyan Embassy - Abd. Elghariani, Kaiss Ali (2014)
E-Scholarship system is a project developed for Students’ Affairs Office in Libyan Embassy. This system will assist the office’s stuff to manage scholarship student’s information and their financial affairs in well-organized way. The main functions of E-scholarship system are maintain student information such as adding new scholarship student, and student’s financial affairs such as student’s salary payment and study fees payment. It also allows the office’s staff to access student’s information easily. Student’s financial information such as the amount of money paid during his/her study will be shown to the academic attached and financial attach any time they require. In this project, software engineering methodology has been adopted and implemented to improve the software development process. Agile methodology specifically XP approach has been used as a software process model. All XP approach phases have been prudently studied and reviewed to be implemented in a proper way. Additionally, the user stories and task description and Class Responsibility Collaborator (CRC) will be documented to be useful for requirement analysis and system design. The sophisticated Microsoft Visual Studio.Net framework has been used as one of the sophisticated tools for programming with Microsoft SQL Server as system's database.